2010
DOI: 10.1097/shk.0b013e3181dc0977
|View full text |Cite
|
Sign up to set email alerts
|

Early Assessment of Leukocyte Alterations at Diagnosis of Septic Shock

Abstract: A dramatic decrease in circulating lymphocyte number is regularly described after septic shock. However, it is unknown how early this alteration develops after diagnosis of shock and if it remains stable over time. Twenty-one septic shock patients with no comorbidities were included within 2 h after the beginning of vasopressive treatment. Flow cytometry phenotyping of circulating leukocyte subpopulations and quantitative real-time polymerase chain reaction of T-bet, GATA-3, FOXP3, and RORγ mRNA were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
114
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 29 publications
17
114
2
5
Order By: Relevance
“…The dramatic fall in WBC and lymphocyte numbers in our study (Table 2) is consistent with the study of Muenzer and colleagues, which reported low WBC numbers and immunosuppression in the two-hit mouse model of CLP plus pneumonia (38), and the decreased T-cell number increased apoptosis in septic humans (39). Boomer and colleagues further showed that immunosuppression was present not only in peripheral blood cells but also locally in organs in patients that died of sepsis (40).…”
Section: Discussionsupporting
confidence: 81%
“…The dramatic fall in WBC and lymphocyte numbers in our study (Table 2) is consistent with the study of Muenzer and colleagues, which reported low WBC numbers and immunosuppression in the two-hit mouse model of CLP plus pneumonia (38), and the decreased T-cell number increased apoptosis in septic humans (39). Boomer and colleagues further showed that immunosuppression was present not only in peripheral blood cells but also locally in organs in patients that died of sepsis (40).…”
Section: Discussionsupporting
confidence: 81%
“…Because circulating IL-7 concentration is mostly regulated by its scavenging rate by T cells, such increased concentration is not surprising in markedly lymphopenic hosts such as septic shock patients (Table I) (4,15).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, sepsis is associated with a severe lymphopenia that also affects circulating NK cells (202). The decreased number of circulating NK cells persists over 1 wk (203).…”
Section: Immune Status Of Nk Cells During Sepsismentioning
confidence: 99%